The Impact of Community-Focused CUREs on Biology Student Identity, Persistence, and Career Outcomes at an HBCU - John W. Curtis; Ashley N. Haines; Nazir Barekzi (Trends in Higher Education)
Course-based undergraduate research experiences (CUREs) have been widely hailed as an innovative approach to engage students in college coursework through exposure to authentic research, leading to improved persistence and more equitable access to research opportunities. This article presents an analysis of the impact of implementing a novel type of CURE across the biology curriculum at one public historically black university, introducing a community focus through a partnership with a local nonprofit organization working to restore a polluted local river. The analysis incorporates survey research on student science identity and sense of belonging with administrative records on persistence to graduation and limited data on graduates’ further education and careers. We find that more of the students who completed these novel CUREs graduated on time with a biology degree than those who did not complete CUREs, and that most biology graduates do go on to use their degrees in further education and/or careers in science or healthcare. We discuss the limitations of our analysis, including the relatively short timeframe covered by our data, the almost incalculable impact of the COVID-19 pandemic, and the retrospective nature of our assessment.